Perovskite Solar Cells with All‐Inkjet‐Printed Absorber and Charge Transport Layers. Issue 2 (1st July 2020) - Schackmar, Fabian; Eggers, Helge; Frericks, Markus; Richards, Bryce S.; Lemmer, Uli; Hernandez‐Sosa, Gerardo; Paetzold, Ulrich W.
Abstract: One of the key challenges of perovskite photovoltaics is the scalable fabrication of high‐efficiency perovskite solar cells (PSCs). Not only the scalable deposition of high‐quality perovskite thin‐films itself, but also the adjacent charge extraction layers is pivotal. In this work, PSCs based on all‐inkjet‐printed absorber and extraction layers are presented, allowing for a scalable and material‐efficient deposition. The inkjet‐printed PSCs are of p–i–n‐architecture with a precursor‐based nickel oxide hole‐transport layer, a high‐quality inkjet‐printed triple‐cation (methylammonium, formamidinium, and cesium) perovskite absorber layer and a double layer electron‐transport layer of phenyl‐C61‐butyric acid methyl ester and bathocuproine. The ink properties, inkjet parameters, and annealing procedure are optimized for each layer. PSCs with such inkjet‐printed absorber and charge carrier extraction layers demonstrate an efficiency of >17% with low hysteresis. Although printed in ambient atmosphere, the devices show excellent short‐term stability (40 h) even under elevated temperature (85 °C). These results are a promising next step on the way to fully inkjet‐printed perovskite solar cells, including both electrodes as well. Abstract : In this work, high efficiency perovskite solar cells based on all‐inkjet‐printed absorber and extraction layers are presented. A detailed report on the ink properties, inkjet, and annealing parameters is given for each layer. Optical and electrical characterization are used to optimize the separate layers for device performance demonstrating unprecedented high power conversion efficiency >17% with low hysteresis and stabilized power output.